Risk factor for pituitary dysfunction in children and adolescents with Rathke's cleft cysts - Han Hyuk Lim; Sei Won Yang (Korean Pediatric Society, 2010)
PurposeThis study evaluated the clinical manifestations of and risk factors for pituitary insufficiency in children and adolescents with Rathke's cleft cysts.MethodsForty-four patients with Rathke's cleft cysts younger than 19 years who visited Seoul National University Children's Hospital between January 1995 and September 2009 were enrolled. Rathke's cleft cysts were confirmed histologically through an operation in 15 patients and by brain magnetic resonance imaging (MRI) in 29 patients. The clinical, hormonal, and imaging features were reviewed retrospectively.ResultsThe clinical presentation of symptomatic patients was as follows: headache (65%), endocrinopathy (61%), and visual disturbance (19%). Endocrinopathy included central precocious puberty (18%), diabetes insipidus (14%), general weakness (11%), and decreased growth velocity (7%). After surgery, hyperprolactinemia resolved in all patients, but growth hormone insufficiency, hypothyroidism, and diabetes insipidus did not improve. Pituitary insufficiency except gonadotropin abnormality correlated significantly with severe headache, visual disturbance, general weakness, and cystic size. Suprasellar extension of cysts and high signals in the T2-weighted image on brain MRI were related to hypothyroidism, hypocortisolism, and diabetes insipidus. Multivariable linear regression analysis showed that only general weakness was a risk factor for pituitary insufficiency (R2=0.549).ConclusionGeneral weakness is a risk factor for pituitary insufficiency in patients with Rathke's cleft cysts. When a patient with a Rathke's cleft cyst complains of general weakness, the clinician should evaluate pituitary function and consider surgical treatment.